Sosialisasi Pengembangan Kebun Buah Nuresy Menjadi Konsep Eduwista - Eva Yanti , Mariana; Sitompul, Hamela Sari; Nasution, Nurhadida (PT. Karya Inovatif Nusantara, 2025)
Edutourism is very suitable to be implemented in agrotourism areas. In addition to getting education, tourists will also be treated to natural beauty and agricultural products. This is the basis for this research to develop edutourism in Nursery Fruit Garden. The development of the Edutourism Concept in Nursery Fruit Garden that will be carried out is grafting edutourism and plant nursery cultivation edutourism. In addition, development will also be carried out in the marketing field to increase visitor enthusiasm and also to increase income. The method used in this study is the best practice analogy. The best practice analogy method is carried out by searching for data and literature studies and benchmarking to determine the image of the Fruit Garden area so that the best image is formed. The results of the research on the development of the edutourism concept that was carried out showed positive results. This can be seen from the increase in the number of visitors and the increase in additional competence of garden managers and field assistants.